2015
DOI: 10.1002/elps.201400299
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and pattern changes of porcine serum apolipoprotein A‐I in four different infectious diseases

Abstract: Apolipoprotein A-I (Apo A-I) is a major protein in lipid/lipoprotein metabolism and decreased serum levels have been observed in many species in response to inflammatory and infectious challenges. Little is known about the porcine homologue, therefore in this work we have characterized it through biochemical and proteomic techniques. In 2DE, porcine serum Apo A-I is found as three spots, the two more acidic ones corresponding to the mature protein, the more basic spot to the protein precursor. Despite high seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Sample preparation for mass spectrometry was performed as recently described . Briefly, spots of interest were washed, destained, reduced and alkylated before in‐gel tryptic digestion (TrypsinGold, Mass Spectrometry Grade, Promega, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Sample preparation for mass spectrometry was performed as recently described . Briefly, spots of interest were washed, destained, reduced and alkylated before in‐gel tryptic digestion (TrypsinGold, Mass Spectrometry Grade, Promega, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the target genes of other DELs ( Supplementary File S8 ), including ENSSSCT00000066793, ENSSSCT00000069743, ENSSSCT00000077515, MSTRG.14478.1, ENSSSCT00000080216, MSTRG.1567.1, MSTRG.4080.9 (target gene: ACACA ), ENSSSCT00000074683, ENSSSCT00000083654, ENSSSCT00000084825, ENSSSCT00000085428, ENSSSCT00000085972, ENSSSCT00000089741, ENSSSCT00000089741, MSTRG.14434.8, MSTRG.14355.1 (target gene: LEP ), ENSSSCT00000066499, MSTRG.10478.1, MSTRG.232.1 (target gene: ACLY ), ENSSSCT00000086039 (target gene: DGAT2 ), ENSSSCT00000050073, ENSSSCT00000088265, MSTRG.12072.1, MSTRG.14478.1 (target gene: PTGR1 ), ENSSSCT00000073662, ENSSSCT00000075506, ENSSSCT00000087125, and MSTRG.5410.1 (target gene: SREBF1 ), are also closely related to fat metabolism [ 29 , 39 ]. KEGG and GO analyses revealed that many fat and cholesterol metabolism-related pathways and terms were significantly enriched, and some genes related to lipid metabolism were enriched multiple times, including APOA1 , APOA4 , APOB , MTTP , ABCG5 , and ABCG8 [ 40 , 41 , 42 , 43 , 44 ]. Furthermore, via trans prediction, we found that ENSSSCT00000062623, ENSSSCT00000069577, ENSSSCT00000069784, ENSSSCT00000075507, ENSSSCT00000077869, MSTRG.129.2, and MSTRG.5755.1 all formed targeting relationships with APOA1 , APOA4 , APOB , MTTP , ABCG5 , and ABCG8 ( Supplementary File S8 ), and the expression levels of these seven DELs were all higher in the high IMF group, suggesting that these DELs might facilitate lipid transport and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…There are a great number of experimental and field studies confirming the use of APP as indicators for various infectious and inflammatory diseases, but only a few studies used APP to diagnose stress in farm animals. Various studies suggest that relationships between different biomarkers and their precursors and combinations thereof allow a more precise definition of pathological processes than is the case with single markers (19–22). CRP and SAA are the first line rapid reacting APPs increasing within hours.…”
Section: Introductionmentioning
confidence: 99%